Changes in selected immunological parameters and antioxidant status of rainbow trout exposed to malachite green (Oncorhynchus mykiss, Walbaum, 1792) - Yonar, M. Enis; Yonar, Serpil Mise (Academic Press Inc Elsevier Science, 2010)
In this study, the effects of malachite green on selected immunological parameters, oxidative stress and antioxidant status biomarkers in blood, liver, kidney, spleen and gill of rainbow trout, Oncorhynchus mykiss, was examined. During 5 days the malachite green was applied at concentrations of 1/15,000 and 1/150,000 for 30s and 60 min, respectively Immunological parameters (nitroblue tetrazolium (NBT) activity, total plasma protein (TP), total immunoglobulin (TI)) and biochemical parameters (lipid peroxidation (MDA), catalase (CAT) activity, reduced glutathione (GSH) levels) were evaluated after exposed to malachite green It has been observed that NBT activity (p < 005. p < 0001). total protein (p < 0.01, p < 0 001) and total immunoglobulin (p < 0 05, p < 0 001) levels were decreased compared with control group In the rainbow tout exposed to malachite green duration 5 days significantly increased lipid peroxidation, which might be associated to decreased levels of reduced glutathione and catalase activity in the whole tissues of O mykiss (p < 0 05, p < 0 01, p < 0 001 for each cases) (C) 2009 Elsevier Inc All rights reserved
Keywords: Rainbow trout; Malachite green; Immunomodulation; Oxidative stress; Antioxidant status